Simmel, Goethe and the Question of Form. Or: the Value of Morphology - Covetti, Giuliano (Simmel Studies)

(untitled) (Edizioni ETS, 2022)
This brief contribution aims to focus Simmel's filtration of goethean morphology. More specifically, here we think that it could be assumed: a) that Simmel implicitly characterized his social studies through a morphological method; b) that this method can be traced back to Goethean studies of natural philosophy. In order to prove it, we take into account: Simmel's The Philosophy of Money, Sociology, Kant and Goethe and Goethe; some goethean passages about natural philosophy. Firstly, we present some theoretical suggestions related to Goethe's morphology; secondly, we give a look to Simmel's morphological approach involved into the study of society. In the end, we draw some conclusions that arise from this comparison.